Photosynthesis and photoprotection in Quercus ilex resprouts after fire - Fleck, I; Hogan, K P; Llorens, L; Abadía, A; Aranda, X (Tree Physiology, 1998)
Plants that resprout after fires often have higher rates of photosynthesis than before a fire. To elucidate the mechanism of this response, we studied gas exchange and chlorophyll fluorescence in Quercus ilex L. plants growing on control (unburned) sites and on sites that had been burned the preceding summer. In early July, photosynthetic rates and stomatal conductance were similar in plants on unburned and burned plots, and in young and old foliage within unburned plots. At this time, photochemical efficiency of photosystem II (PSII), nonphotochemical quenching of chlorophyll fluorescence (NPQ), and the de-epoxidation of violaxanthin to zeaxanthin were also similar among leaves of different ages and treatments. In late July, photosynthetic rates and stomatal conductances were much greater in resprouts on the burned areas than in unburned plants. From early to late July, unburned plants showed an increase in NPQ and the de-epoxidation of violaxanthin to zeaxanthin, indicating increased photoprotection as a result of enhanced nonradiative dissipation of excess light energy. Plants on the burned plots did not show these changes. Leaves of all ages and treatments showed no substantial reduction in potential quantum yield of PSII (Fv/Fm) at midday or predawn, indicating that there was little or no photoinhibition. Leaf nitrogen and soluble protein contents varied with leaf age during July, but did not vary between treatments. We conclude that the primary effect of burning is an increase in water availability to resprouting plants that eliminates the need for photoprotection, at least in the short term. The decrease in photosynthetic rates of unburned leaves in late July was the result of reduced stomatal conductance. We suggest that lowered stomatal conductance is the primary limiting factor in Q. ilex leaves, governing the regulation of carboxylation activity and energy dissipation processes.
10.1093/treephys/18.8-9.607
Keywords: chlorophyll fluorescence; Gas exchange; Holm oak; photoinhibition; Photosystem II; zeaxanthin

Influence of fire and tree-fell on physiological parameters in Quercus ilex resprouts - Fleck, I; Grau, D; Sanjosé, M; Vidal, D (Ann. For. Sci., 1996)
Variations in the physiology of two kinds of resprout (originated after fire and after tree-fell) of Quercus ilex were analyzed under field conditions and compared with respect to the original, undisturbed vegetation, located within a Mediterranean watershed (northeast Spain). Resprouting vegetation of Quercus ilex after fire or after tree-fell showed, during the next growing seasons, enhanced photosynthesis, leaf conductance and Rubisco activity with respect to the original vegetation, especially under high temperature, irradiance and vapor pressure deficit (VPD). The lack of differences in nutrient (N,C,P,K and Ca) and soluble carbohydrate concentrations in leaves of resprouts originated after fire or after tree-fell indicates the independence of nutrients released by the action of fire and the contribution of underground organs. Differences in leaf mass per area (LMA) were due to increased thickness in resprouts whereas density was the same. N investment in chlorophylls or Rubisco was not different in control or either kind of resprout. The increased amount of carotenoids in resprouts contributed to providing protection from photoinhibitory processes
Keywords: fire; Gas exchange; Nutrients; photosynthetic pigments; Quercus ilex; tree-fell